IDENTIDADES AL MARGEN Y EN LOS MÁRGENES. FRONTERA Y LABERINTO EN ARRAIANOS (ELOI ENCISO, 2012) - Fernando REDONDO NEIRA (Fonseca, Journal of Communication, 2023)
The film studied here, Arraianos (Eloi Enciso, 2012), runs around a crossroad where the fictional and documentary converge, where a strong anti-naturalistic representation of a space and the human group that inhabits it are compared, and a willingness to visual inquiry into that space where traces of a mythical past that has been forming it still remains. Built on the material of the physical space that explores and interrogates, Arraianos displays a speech, also built on the telluric and the popular, it strives to realize the frontier character of that place, A Raia, between Galicia and Portugal, limit territory that has managed to build its own identity.